ANALYSIS OF THE HEALTH OF INDONESIAN SHARIA BANK USING THE RGEC METHOD FOR THE YEAR 2021-2022 - Ramansyah, Dian; Isnaeni, Nurida; Lubis, Paulina (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine the soundness level of Indonesian Sharia Banks in 2021-2022 using the measurement method stipulated in the Financial Services Authority Regulation No.8/POJK.03/2014 concerning Assessment of the Soundness Level of Sharia Commercial Banks and Sharia Business Units using the RGEC method. The assessment factors in the RGEC method are the Risk Profile, Good Corporate Governance, Earnings and Capital factors. The research used is quantitative research with a descriptive approach. This type of research is intended to obtain information regarding bank health based on the quarterly financial reports of Bank Syariah Indonesia for 2021-2022. In this study the data used are secondary data in the form of financial reports and GCG implementation reports. The data analysis technique used in this study is a descriptive data analysis technique by analyzing financial reports using the RGEC method. The results of the study show that the soundness level of Bank Syariah Indonesia from 2021 to 2022 has received the title of